(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
In recent years the subject of pharmacological cognitive enhancement has been taking on increasing significance. The article seeks to concentrate on the problem of the informed consent of the patient, in the case of the medical prescription of off-label drugs for cognitive enhancement and the potential legal consequences for the doctor in the event of harm – or the death of the patient. Indeed, many off-label drugs taken for purposes other than that for which it had been tested, have been seen to have the potential to cause side effects, resulting in illness (i.e. harm) some quite serious such as, for example, depressive syndromes, frequent migraines, and changeable moods.